British first world war propaganda: from A to Z - Paddock, Troy (First World War Studies, 2026)
Keywords: dept.his

Melissa Reynolds. Reading Practice: The Pursuit of Natural Knowledge from Manuscript to Print - Petto, Christine (The American Historical Review, 2025)
Keywords: Knowledge production; Knowledge-based systems; Natural (archaeology); Traditional knowledge; dept.his

Meredith L. McCoy. On Our Own Terms: Indigenous Histories of School Funding and Policy - Amerman, Steve (The American Historical Review, 2025)
Keywords: Indigenous; Indigenous culture; dept.his

Bamboo in Vietnam: an anthropological and historical approach, written by ðinh Trọng Hiếu and Emmanuel Poisson - Thompson, C. (East Asian Science Technology and Medicine, 2025)
Keywords: Ancient history; Anthropology; Archaeology; Asian studies; Bamboo; Biology; Botany; China; History; Medicine; Sociology; Traditional medicine; dept.his

Finding the Sweet Spot: Wild Bees, Indigenous Peoples, and the Historic Trade in Honey and Beeswax in Northern Vietnam - Thompson, C. Michele (Asian Medicine, 2026)
When most people think of the use of animals in traditional systems of medicine, what springs to mind is one kind or another of megafauna such as rhinoceros, bears, sharks, and others. Sometimes more mundane creatures such as pangolins are included. However, invertebrates and substances produced by them have been used in Asian systems of medicine since the earliest records of materia medica from the region were created. Animals used range from shellfish and crustaceans to various insects and insect products such as cocoons, honey, and beeswax. In terms of their role in the food chain, and as pollinators, invertebrates are as crucial to the health, indeed the survival, of ecosystems in Asia and elsewhere as are megafauna. Loss and degradation of habitat is probably affecting more invertebrates than medicalization. Still, the expansion of medicalization in Asia and beyond is contributing to the danger many populations of invertebrates currently face. This article gives an overview of the place of invertebrates in Vietnamese traditional medicine and then presents a case study of two varieties of honey- and beeswax-producing bees found in northern mainland Southeast Asia and southern China: Apis dorsata F. and Apis cerana. © C. Michele Thompson, 2026. Published with license by Koninklijke Brill BV
Keywords: Arthropod; Asian traditional medicine; Creatures; Habitat; Invertebrate; Mainland; Mainland China; Southeast asia; Vietnamese; Vietnamese medicine; bees; beeswax; dept.his; ecological damage; endangered species; honey; invertebrates

‘A small measure of fairness’: Black South Africans and the Courts, 1919–1938 - Eastman, Michael; Feinberg, Harvey (Journal of Southern African Studies, 2025)
Keywords: Computer science; Measure (data warehouse); Political science; Sociology; South Africa; administration of justice; appeals; courts; criminal justice; dept.his; judges; justice for Africans; magistrates; reviews

Changing Working Environments in Philosophy: Reflections from a Case Study - McConwell, Alison; Bogacz, Magdalena; Brecevic, Char; Haber, Matthew; Wu, Jingyi; Roe, Sarah (Philosophy of Science, 2025)
Abstract There is an “underrepresentation problem” in philosophy departments and journals. Empirical data suggest that while we have seen some improvements since the 1990s, the rate of change has slowed down. Some posit that philosophy has disciplinary norms making it uniquely resistant to change. We present results from an empirical case study of a philosophy department that achieved and maintained male-female gender parity among its faculty as early as 2014. Our analysis extends beyond matters of gender parity because that is only one, albeit important, dimension of inclusion. We build from the study to reflect on strategies that may catalyze change.
Keywords: Computer science; Epistemology; Philosophy; Sociology; dept.his; peer-reviewed

Matthew Fontaine Maury: Pathfinder - Smith, Jason W (International Journal of Maritime History, 2016)
Historians have long recognized Matthew Fontaine Maury as an important if controversial figure in the histories of science and of maritime and naval affairs. These assessments, however, rest on scholarship that is by now more than a half-century old. It is therefore appropriate to look at Maury’s significance from fresh perspectives, incorporating recent historiographical trends in the history of science and cartography, environmental history, cultural history and military history. This article focuses on the ways in which Maury’s cartographic work reframed mariners’ understanding of the marine environment away from what he perceived to be a watery wilderness towards an ordered environment safe and favourable to American commerce. Maury was long known as ‘The Pathfinder of the Seas’, but I argue that his significance, in fact, lies in the ways he and his staff at the Naval Observatory organized the sea as a ‘common highway’, tracing paths, but also imposing narratives and constructing new meanings. Maury’s tool was the nautical chart and, particularly, his Wind and Current Charts series that by the 1850s reimagined the ways mariners, navigators and naval officers understood and harnessed the ocean environment. The article briefly considers these charts from three perspectives – method, process and representation – in order to see the ways in which Maury was pushing the boundaries of the cartographic medium to usher in revolutionary ways of envisioning the ocean environment. By quantifying winds, symbolizing whales and infusing the sea with ship tracks, among other things, Maury was imposing potent, if sometimes flawed, new ways of understanding and imagining the sea that were central to American maritime expansion in the antebellum era. In this and other ways, we can see Maury anew, a figure central to the growth of American commercial empire and to new ways of understanding and thinking about the sea.
Keywords: dept.his

Community and identity in Castilian histories of the fifteenth century - Kern, Darcy (Sharq al-Andalus, 2021)
La historia fue tan importante para la construcción de la identidad comunitaria y la legitimidad política en el siglo XV como lo es hoy, y en los reinos de España igualmente tenso. Los cronistas y biógrafos católicos castellanos parecen inseguros del estado preciso de los moros en Iberia. Todos estaban de acuerdo con el control político o el señorío de los cristianos castellanos, pero pocos tenían una idea clara de las implicaciones de ese señorío para los moros. ¿Debería permitirse a los moros permanecer como parte de la comunidad una vez que un monarca cristiano castellano tomara el control de su ciudad, región o reino, o no había posibilidad de que pertenecieran? Rodrigo Sánchez de Arévalo (1404-1470), Fernán Pérez de Guzmán (c. 1377-c. 1460), Alonso Fernández de Palencia (1423-1492), Hernando de Pulgar (1436-c. 1492), y Mosén Diego de Valera (1412-1488) dieron diferentes respuestas. Todos coincidieron en que la comunidad castellano-leonesa existía antes de al-Andalus y, por lo tanto, era la comunidad política legítima de Hispania. La mayoría de ellos aceptaron la presencia de Granada de facto pero no de jure. Sin embargo, Arévalo, Valera y Pulgar sugieren la posibilidad de una comunidad política musulmana de jure bajo dominio castellano; Palencia y Guzmán no.
Accepted: 2021-07-14T06:58:23Z
Keywords: dept.his

Umayyad Caliphate - Judd, Steven C. (The Encyclopedia of Empire, 2016)
The Umayyad Caliphate (661–750) was the first Islamic dynasty. Muʿawiya ibn Abi Sufyan established himself as caliph in Damascus after his victory over ʿAli ibn Abi Talib in the civil war that followed the murder of ʿUthman ibn ʿAffan in Medina. Muʿawiya and his successors expanded the territory under Muslim rule dramatically. At their peak, the Umayyads ruled an empire stretching from Spain to the frontiers of China and India. The Umayyads made significant contributions to the development of the Islamic faith and to the spread of the Arabic language throughout the region. Dynastic crises, revenue shortfalls, and the limitations of an empire based on conquest ultimately led to their demise at the hands of the Abbasids in 750.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118455074.wbeoe178
Keywords: 6th–10th centuries; Islam; Late Antiquity; Western Asia; dept.his; history; northern Africa; religious history

A Fantasy in Fashion: African American Empowerment in an Era of Opulence - Carter-David, Siobhan; Wu, Ellen (Race and Retail: Consumption across the Color Line, 2015)
Race has long shaped shopping experiences for many Americans. Retail exchanges and establishments have made headlines as flashpoints for conflict not only between blacks and whites, but also between whites, Mexicans, Asian Americans, and a wide variety of other ethnic groups, who have at times found themselves unwelcome at white-owned businesses. Race and Retail documents the extent to which retail establishments, both past and present, have often catered to specific ethnic and racial groups. Using an interdisciplinary approach, the original essays collected here explore selling and buying practices of nonwhite populations around the world and the barriers that shape these habits, such as racial discrimination, food deserts, and gentrification. The contributors highlight more contemporary issues by raising questions about how race informs business owners’ ideas about consumer demand, resulting in substandard quality and higher prices for minorities than in predominantly white neighborhoods. In a wide-ranging exploration of the subject, they also address revitalization and gentrification in South Korean and Latino neighborhoods in California, Arab and Turkish coffeehouses and hookah lounges in South Paterson, New Jersey, and tourist capoeira consumption in Brazil. Race and Retail illuminates the complex play of forces at work in racialized retail markets and the everyday impact of those forces on minority consumers. The essays demonstrate how past practice remains in force in subtle and not-so-subtle ways.
Keywords: dept.his

Receiving more: Utopia in Spain and new Spain - Kern, D. (The Oxford Handbook of Thomas More's Utopia, 2023)
Keywords: dept.his

Book Review: Aro Velmet, Pasteur’s Empire: Bacteriology & Politics in France, Its Colonies, & the World (New York: Oxford University Press, 2020), pp. xiv + 306, $78.00, hardback, ISBN: 9780190072827. - Thompson, C. Michele (Medical History, 2022)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0025727321000508/resource/name/firstPage-S0025727321000508a.jpg
Keywords: dept.his

Book Review: Edington, Claire E. – Beyond the Asylum: Mental Illness in French Colonial Vietnam. - Thompson, C. Michele (Histoire sociale / Social History, 2023)
Number: 115
Keywords: book.review; dept.his

Book Review: Epidemic Politics in Contemporary Vietnam: Public Health and the State By Martha Lincoln, London: Bloomsbury Academic. 2022. 232 pp.1 - Thompson, C. Michele (Medical Anthropology Quarterly, 2024)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/maq.12840
Keywords: book.review; dept.his

Jean Marie Despiau: Unjustly Maligned Physician in the Medical Service of the Nguyen - Thompson, C. Michele (Vietnam and the West, 2010)
Keywords: dept.his

Swarms, Herds, and Peoples: Examinations of Interspecies Dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
Gale OneFile includes Swarms, Herds, and Peoples: Examinations of Interspecie by David A. Bello and C. Michele Thompson. Click to explore.
Keywords: dept.his

Fighting for health: medicine in cold war Southeast Asia - Thompson, Claudia Michele; Sweet, Kathryn; Aso, Michitake (NUS Press, 2024)
Keywords: 20th century; Cold War; Medicine; 20th century; Medical care; 20th century; Medical policy; History; History; Public Health; Public health; Southeast Asia; dept.his; history; Health Policy; history; History of Medicine; Southeast Asia; Asia; Southeastern

The Duke of Lennox, 1574 1624: A Jacobean Courtier s Life. David Bergeron. Edinburgh: Edinburgh University Press, 2022. x + 244 pp. $110 - Kern, Darcy (Renaissance Quarterly, 2023)
Keywords: book.review; dept.his

The many currents of antebellum maritime empire - Smith, Jason W. (Diplomatic History, 2023)
Keywords: dept.his; peer-reviewed

Costa Rica after Coffee: The Co-op Era in History and Memory - Kordick, Carmen (Agricultural History, 2023)
Num Pages: 3
Keywords: book.review; dept.his

Aspects of Greek-Russian Relations in the Early Modern and Modern Periods (17th-20th Centuries) - Chrissidis, Nikolaos (Annuaire de l'École pratique des hautes études (EPHE), Section des sciences religieuses. Résumé des conférences et travaux, 2023)
This series of four presentations sought to examine case studies of Greek-Russian relations in the early modern and, mostly, modern period. In the choice of topics, I was guided by two considerations: first, I sought to highlight topics that, to my mind, have not yet attracted the attention they deserve in historiography. For example, although alms collections in the Russian Empire in the early modern period have been discussed repeatedly, this has not been the case until quite recently for t...
ISBN: 9782909036519 Number: 130
Keywords: Christianisme orthodoxe; Histoire des chrétiens d’Orient (XVIe-XXIe siècle); dept.his

Russia in the German global imaginary: imperial visions and utopian desires, 1905-1941 - Paddock, Troy (First World War Studies, 2023)
Num Pages: 2
Keywords: book.review; dept.his

Siyar: An Ephemeral Genre of Islamic Legal Literature? - Judd, Steven (Islam on the Margins, 2022)
Section: Islam on the Margins
Keywords: History & Culture; Middle East and Islamic Studies; Religion in Asia; Religious Studies; dept.his

Islam on the Margins: Studies in Memory of Michael Bonner - Judd, Steven; Haug, Robert (BRILL, 2023)
Islam on the Margins commemorates the contributions Michael Bonner made to Near Eastern Studies. It consists of fourteen contributions by his students and colleagues that focus on various aspects of his work. The contributions coalesce around four major themes of Bonner’s endeavours: Holy War and the Frontier, Qurʾan and Law, Geography and Ethnography, and Books, Coins and Titles. Collectively, the contributions underscore the breadth of Michael Bonner’s erudition and impact on the field.
Google-Books-ID: JQqtEAAAQBAJ
Keywords: History / Asia / General; History / Middle East / General; Religion / Islam / General; dept.his

'Abd al-Rahman b. 'Amr al-Awza'i - Judd, Steven C. (Simon and Schuster, 2019)
‘Abd al-Rahman b. ‘Amr al-Awza‘i (c.707–774) was Umayyad Syria’s most influential jurist, part of a generation of scholars who began establishing the first formal structures for the preservation and dissemination of religious knowledge. Following the Abbasid revolution, they provided a point of stability in otherwise unstable times. Despite his close ties to the old regime, al-Awza‘i continued to participate in legal and theological matters in the Abbasid era. Although his immediate impact would prove short-lived, his influence on aspects of Islamic law, particularly the laws of war, endures to this day.
Google-Books-ID: LknmDwAAQBAJ
Keywords: Biography & Autobiography / Historical; History / General; History / Middle East / General; Law / Islamic; Religion / History; Religion / Islam / General; Religion / Islam / Theology; Social Science / Islamic Studies; dept.his

The Cassock Does Not a Monk Make. Or Does It? Fake and Real Monks from the Orthodox East in the Russian Empire (19th — Early 20th Сentury) - Chrissidis, Nikolaos (Istoriya, 2023)
Monastic tonsure of citizens of the Russian Empire abroad became a particularly complex issue during the latter half of the nineteenth century, when Mt. Athos became a favorite destination of those interested in assuming the monastic habit outside the empire. The Russian authorities sought to control and regulate such tonsures by establishing procedures for checking their validity, and by ruling out automatic recognition of them in the empire. Individuals who were tonsured as monks abroad manipulated or tried to manipulate such regulations in order to facilitate travel back and forth from the Russian Empire for their own purposes. The result was that the real and apparent ambiguities that such rules allowed for were exploited by both state authorities and by real or fake monks themselves. The essay seeks to offer some perspectives on this phenomenon by focusing on four cases preserved in archival records. © 2023 Ltd "Integration: Education and Science". All rights reserved.
0 citations (Crossref) [2023-10-31]
Keywords: Mount Athos; St. Panteleimon Monastery; dept.his; fake monks; monasticism; peer-reviewed; tonsures abroad

Sabbatical leave report: Fall 2013 - Nakamura, Byron (Distribution: Fall 2013 ; History., 2013)
This leave was devoted to research and revision of two conference papers submitted for publication, and to revision of a book chapter on boxing in the antiquity The chapter was submitted and accepted for publication in the Cambridge Companion to Boxing series.
Keywords: dept.his; faculty_collection; sabbatical_report

The Lion and the Lily: Map and Atlas Production in Early Modern England and France. - Petto, Christine Marie (2011)
Dr. Petto completed chapters 2 and 3 and a book proposal for her second manuscript, The lion and the lily: map and atlas production in early modern England and France. Chapter 2 describes local mapping and hydrographic charting initiatives in the 17th and 18th century; chapter 3 focuses on scientific cartography and the efforts of both crowns to map colonial interests in the Americas and Asia. She obtained book contract with Lexington Books, with release date of July 2013.
Keywords: dept.his; faculty_collection; sabbatical_report

Friday Night Fighter: "Indio" Ortega and the Golden Age of Televised Boxing. - Rondinone, Troy (Spring ; History., 2011)
Keywords: dept.his; faculty_collection; sabbatical_report

A History of Smallpox and Preventive Treatments for It in the Lands Bordering the South China Sea - Thompson, C. Michele (2011)
Keywords: dept.his; faculty_collection; sabbatical_report

Womanpower in the 1960's, Fabian Feminism. - Beals, Polly (2009)
Worked on book about Fabian feminism. Finished the final chapter but book isn't complete yet. Wrote and delivered paper in London in March 2009. Is expanding book to include 1980's and 1990's Fabian feminism.
Keywords: dept.his; faculty_collection; sabbatical_report

Eighteenth-Century Russia. - Chrissidis, Nikolaos (2008)
Worked on a book and wrote and presented several paper on eighteenth century Russia.
Keywords: dept.his; faculty_collection; sabbatical_report

American Social Credit Movement. - Kalk, Bruce H. (2006)
Keywords: dept.his; faculty_collection; sabbatical_report

When France was King of 'Kartographie' - Petto, Christine Marie (2005)
Keywords: dept.his; faculty_collection; sabbatical_report

Northern Treasures and Southern Essences, an Exploration of Vietnamese Traditional Medicine. - Thompson, C. Michele (2004)
Keywords: dept.his; faculty_collection; sabbatical_report

The Khārijites in Early Islamic Historical Tradition: Heroes and Villains. By HANNAH-LENA HAGEMANN. Edinburgh: EDINBURGH UNIVERSITY PRESS, 2021. Pp. xii + 316. $110, £85 - Judd, Steven C. (Journal of the American Oriental Society, 2023)
0 citations (Crossref) [2023-10-31]
Keywords: book.review; dept.his

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge/Taylor & Francis Group, 2020)
Keywords: Causes; Historiography; Historiography; World War; 1914-1918; World War; 1914-1918; dept.his; faculty_collection

The Saints of Progress: A History of Coffee, Migration, and Costa Rican National Identity - Kordick, Carmen (The University of Alabama Press, 2019)
"This work narrates the development of a historically remote–although internationally celebrated–coffee-growing region from the early 19th century through to the first decade of the 21st century. It considers the nation-building process from the margins to question traditional scholarly works that have reproduced, rather than deconstructed, Costa Rica's exceptionalist national mythologies that imagine this isthmian republic as Central America's 'white,' democratic, nonviolent, and egalitarian republic. The book recognizes that even though Costa Rica's exceptionalist rendition draws on some undeniable realities, it thoughtfully considers the origins, applicability, and longevity of the different elements of this exceptionalist master narrative. In particular, it suggests the mythology emerged during the Cold War, as revolution, civil war, military dictatorship, and state violence plagued much of Central America. In this same period, Costa Rica not only retained a relatively stable democratic system, but policymakers eliminated the standing army in 1948. This widely embraced and celebrated historical narrative, however, distorts as much as it illuminates the experience of contemporary and historical actors"–
Keywords: Coffee industry; Costa Rica; Costa Rica; History; Political aspects; dept.his

Sabbatical report on Contesting the Origins of the First World War - Paddock, Troy R. E. (2019)
Dr. Paddock spent the year completing a book and revising an article.
Keywords: dept.his; faculty_collection; sabbatical_report

Nightmare Factories The Asylum in the American Imagination - Rondinone, Troy (Johns Hopkins University Press, 2019)
Keywords: History; History; Asylums; Psychiatric hospitals; United States; dept.his; faculty_collection

To Master the Boundless Sea: The U.s. Navy, the Marine Environment, and the Cartography of Empire - Smith, Jason W. (University of North Carolina Press, 2018)
"As the United States grew into an empire in the late nineteenth century, notions like 'sea power' derived not only from fleets, bases, and decisive battles, but also from a scientific effort to understand and master the ocean environment. Beginning in the early nineteenth century and concluding in the first years of the twentieth, Jason W. Smith tells the story of the rise of the U.S. Navy and the emergence of American ocean empire through its struggle to control nature. In vividly told sketches of exploration, naval officers, war, and, most significantly, the ocean environment, Smith draws together insights from environmental, maritime, military, and naval history, and the history of science and cartography, placing the U.S. Navy's scientific efforts within a broader cultural context"–
SCSU Faculty Scholar Award
Keywords: History; Naval; History; Cartography; Imperialism and science; United States; History; Nautical charts; SCSU Faculty Scholar Award; United States; United States. Navy; award_winner; dept.his; faculty_collection

Human Rights in the People's Republic of China - Wu, Yuan-li; Chang, Maria Hsia; Cooper, John F.; Gregor, A. James; Michael, Franz H.; Lee, Ta-ling (Routledge, 2018)
Keywords: 20th century; Human rights; 21st century; China; History; Human rights; dept.his; faculty_collection

New Perspectives on Ibn ʻAsākir in Islamic Historiography - Judd, Steven C.; Scheiner, Jens J. (Brill, 2017)
This volume contains six articles on Ibn 'Asākir and his 'Ta'rīkh madīnat Dimāshq' illustrating a variety of perspectives and approaches to the material. It includes a seventh article that discusses the process by which the now standard 'Dār al-fikr' edition was compiled. The contributions address both the geographical and biographical sections of the 'Ta'rīkh madīnat Dimashq'. Some of the authors examine Ibn 'Asākir's sources, while others describe how Ibn 'Asākir's works were used by later generations of scholars and how he influenced multiple genres of later writings. The volume also contains analyses of individual biographies and discussions of Ibn 'Asākir's treatment of larger classes of people, including the first analysis of his biographies of women. In sum, it illustrates both the wide range of topics that the 'Ta'rīkh madīnat Dimashq' covers and the latest techniques for analyzing Ibn 'Asākir and his work.
Keywords: Historiography; Ibn ʻAsākir; ʻAlī ibn al-Ḥasan; 1105-1176. Tārīkh madīnat Dimashq; Islamic Empire; dept.his; faculty_collection

This City Belongs to You: A History of Student Activism in Guatemala, 1944-1996 - Vrana, Heather A. (University of California Press, 2017)
"Between 1944 and 1996, Guatemala experienced a revolution, counterrevolution, and civil war. In the middle of these national shifts were students from Guatemala's only public university, the University of San Carlos (USAC). USAC students served in, advised, protested, and were later persecuted by the government, all the while crafting a powerful student nationalism founded on their responsibility to lead the nation. In no other moment has the relationship between the university and the state been so mutable, yet so mutually formative. By showing how the very notion of the middle class in Guatemala emerged from these student movements, this book places an often-marginalized region and period at the center of histories of class, protest, and youth movements, while providing an entirely new way to think about the role of universities and student bodies in the formation of liberal democracy throughout Latin America.
Keywords: 20th century; Guatemala; History; Student movements; dept.his; faculty_collection

An Academy at the Court of the Tsars: Greek Scholars and Jesuit Education in Early Modern Russia - Chrissidis, Nikolaos A. (NIU Press, 2015)
Keywords: 17th century; 17th century; Education; Higher; 17th century; Greeks; Education; History; History; Jesuits; Leichoudēs; Iōannikios; 1633-1717; Leichoudēs; Sōphronios; 1652-1730; Moskovskai︠a︡ slavi︠a︡no-greko-latinskai︠a︡ akademii︠a︡; Moscow; Russia; Russia (Federation); dept.his; faculty_collection

Our Land, Our Life, Our Future: Black South African Challenges to Territorial Segregation, 1913-1948 - Feinberg, Harvey M. (Unisa Press, 2015)
Keywords: 1909-1961; History; History; South Africa; Land reform; Law and legislation; South Africa; dept.his; faculty_collection

Major Problems in American Indian History: Documents and Essays - Hurtado, Albert L.; Iverson, Peter; Bauer, William J.; Amerman, Stephen Kent (Cengage Learning, 2015)
Keywords: History; History; Indians of North America; Indians of North America; Sources; dept.his; faculty_collection

Mapping and Charting in Early Modern England and France: Power, Patronage, and Production - Petto, Christine Marie (Lexington Books, 2015)
Keywords: Cartography; England; France; History; History; Cartography; History; Map industry and trade; Paris; dept.his; faculty_collection

Vietnamese Traditional Medicine: A Social History - Thompson, Claudia Michele (NUS Press, 2015)
SCSU Faculty Scholar Award
Keywords: History; Medicine; Chinese; History; Vietnam; Medicine; Traditional; SCSU Faculty Scholar Award; Vietnam; award_winner; dept.his; faculty_collection; history; Medicine; Chinese Traditional; history; Smallpox; prevention & control; Traditional medicine

World War I and Propaganda - Paddock, Troy R. E. (Brill, 2014)
Keywords: Propaganda; World War; 1914-1918; dept.his; faculty_collection

Dr. Ruth A. Parmelee and the Changing Roll of Near East Missionaries in Early Twentieth Century Turkey - Metaxas, Virginia (Role of the American Board in the World: Bicentennial Reflections on the Organization's Missionary Work, 1810-2010, 2012)
The American Board of Commissioners for Foreign Missions (ABCFM) was the country's first creator of overseas Christian missions. Founded in 1810 and supported by a coalition of Calvinist denominations, the ABCFM established the first American missions in India, China, Africa, Oceania, the Middle East, and many other places. It was America's largest missionary organization in the nineteenth century, and its influence was immense. Its missionaries established the first Western schools and hospitals in many parts of the world, and they successfully promoted women's rights and other ideals from the Enlightenment. They also transformed oral languages such as Zulu, Hawaiian, and Cherokee into written form, and they preserved many elements of premodern cultures (albeit not always intentionally). The contributors to this book provide valuable insights on the work of the ABCFM (which exists today under a different name). Some of the contributors profile the lives of notable ABCFM missionaries, others focus on ideological shifts within the Board, and still others chronicle the Board's role in historic events, including the Opium Wars, the colonization of Hawai'i, and the Armenian Genocide. From reading this book, people will come to understand why the ABCFM is widely viewed as America's most historically significant missionary organization.
Keywords: American Board of Commissioners for Foreign Missions; History; Congregational churches; Missions; Missions; American; dept.his; faculty_collection

Southern Medicine for Southern People Vietnamese Medicine in the Making - Monnais-Rousselot, Laurence; Thompson, Claudia Michele; Wahlberg, Ayo (Cambridge Scholars Pub., Cambridge Scholars Publishing, 2012)
What is a national medicine? What does it mean for a medicine to be traditional and scientific at the same time? How could a specifically Vietnamese medicine emerge out of the medical practices and treatments that have flourished and waned during key soci
Keywords: History; Traditional medicine; Vietnam; Vietnam; Traditional medicine; dept.his; faculty_collection

Religion and Identity in Russia and the Soviet Union A Festschrift for Paul Bushkovitch - Chrissidis, Nikolaos A. (Slavica Publishers, Slavica, 2011)
Keywords: Bushkovitch; Paul; Nationalism; History; Christianity and politics; History; Identity (Psychology); History; Nationalism; History; Soviet Union; Politics and government; Politics and government; Russia; Religious aspects; Russia; Russkai͡a pravoslavnai͡a t͡serkovʹ; National characteristics; Russian; Soviet Union; dept.his; faculty_collection

We Will Be Satisfied with Nothing Less: The African American Struggle for Equal Rights in the North During Reconstruction - Davis, Hugh (Cornell University Press, 2011)
Historians have focused almost entirely on the attempt by southern African Americans to attain equal rights during Reconstruction. However, the northern states also witnessed a significant period of struggle during these years. Northern blacks vigorously protested laws establishing inequality in education, public accommodations, and political life and challenged the Republican Party to live up to its stated ideals. In "We Will Be Satisfied With Nothing Less," Hugh Davis concentrates on the two issues that African Americans in the North considered most essential: black male suffrage rights and equal access to the public schools. Davis connects the local and the national; he joins the specifics of campaigns in places such as Cincinnati, Detroit, and San Francisco with the work of the National Equal Rights League and its successor, the National Executive Committee of Colored Persons. The narrative moves forward from their launching of the equal rights movement in 1864 to the "end" of Reconstruction in the North two decades later. The struggle to gain male suffrage rights was the centerpiece of the movement's agenda in the 1860s, while the school issue remained a major objective throughout the period. Following the ratification of the Fifteenth Amendment in 1870, northern blacks devoted considerable attention to assessing their place within the Republican Party and determining how they could most effectively employ the franchise to protect the rights of all citizens.– Book jacket.
Keywords: 1863-1877; African Americans; 19th century; Equality before the law; 19th century; Reconstruction (U.S. history; 1865-1877); African Americans; Civil rights; History; United States; dept.his; faculty_collection

Urban Indians in Phoenix schools, 1940-2000 - Amerman, Stephen Kent (University of Nebraska Press, 2010)
"In the latter half of the twentieth century, tens of thousands of Native American families moved to cities across the United States, some via the government relocation program and some on their own. In the cities, they encountered new forms of work, entertainment, housing, and education. In this study, Stephen Kent Amerman focuses on the educational experiences of Native students in urban schools in Phoenix, Arizona, a city with one of the largest urban Indian communities in the nation. The educational experiences of Native students in Phoenix varied over time and even in different parts of the city, but interactions with other ethnic groups and the experience of being a minority for the first time presented distinctive challenges and opportunities for Native students., Using oral histories as well as written records, Amerman examines how the Phoenix schools tried to educate and assimilate the Native students alongside Hispanic, Asian, black, and white students and how Native children, their parents, and the Indian community at large responded to this new urban education and the question of their cultural identity. Reconciling these pressures was a struggle, but many found resourceful responses, charting paths that enabled them to acquire an urban education while still remaining Indian."–Pub. desc.
SCSU Faculty Scholar Award
Keywords: 20th century; 20th century; Education; 20th century; Indians of North America; 20th century; Public schools; 20th century; Urban schools; 20th century; Urbanization; Arizona; Cultural assimilation; Education; History; Indians of North America; Phoenix; Social aspects; award_winner; dept.his; faculty_collection

The Great Industrial War Framing Class Conflict in the Media, 1865-1950 - Rondinone, Troy (Rutgers University Press, 2010)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers. Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported.
Keywords: History; History; Social conflict; Labor disputes; United States; dept.his; faculty_collection

The System: The American Constitution in Historical Perspective 1763-1929 - Gerber, Richard A. (Cengage Learning, 2009)
Keywords: United States; United States. Constitution; Constitutional history; dept.his; faculty_collection

Revolution and Union: The American Dilemma 1763-1877 - Gerber, Richard A. (Cengage Learning, 2008)
Keywords: History; Textbooks; United States; dept.his; faculty_collection

The Civil Rights Act of 1875: A Reexamination - Gerber, Richard A.; Friedlander, Alan (Connecticut Academy of Arts and Sciences, 2008)
Keywords: Civil rights; History; History; African Americans; United States; dept.his; faculty_collection

Not Your (founding) Fathers' Constitution: Teaching United States Constitutional History - Gerber, Richard A. (The Connecticut Urban Consortium ; New Haven Public Schools, 2007)
Synopsis of the lectures presented during the three-year program, together with a PowerPoint presentations on CD-ROM. This material can be used for preparation of classroom instructional program or directly in the classroom.
Keywords: History; Study and teaching; Study and teaching; Constitutional history; United States. Constitution; United States; United States; dept.his; faculty_collection

When France Was King of Cartography: The Patronage and Production of Maps in Early Modern France - Petto, Christine Marie (Lexington Books, 2007)
When France Was King of Cartography investigates over a thousand maps and nearly two dozen map producers, analyzes the map as a cultural artifact, map producers as a group, and the array of map viewers over the course of two centuries in France. The book focuses on situated knowledge or 'localized' interests reflected in these geographical productions. Through the lens of mapmaking, it examines the relationship between power and the practice of patronage, geography, and commerce in early modern France.
SCSU Faculty Scholar Award
Keywords: 17th century; Cartography; 17th century; Map industry and trade; 18th century; 18th century; Map industry and trade; Cartography; France; History; SCSU Faculty Scholar Award; award_winner; dept.his

Crisis of the Black Intellectual - Wright, W. D. (Third World Press, 2007)
Keywords: African American intellectuals; African Americans; Intellectual life; dept.his; faculty_collection

Black History and Black Identity: A Call for a New Historiography - Wright, W. D. (Praeger, 2002)
Keywords: African Americans; Historiography; African Americans; Race identity; dept.his; faculty_collection

The Origins of the Southern Strategy: Two-Party Competition in South Carolina, 1950-1972 - Kalk, Bruce H. (Lexington Books, 2001)
Keywords: 1951-; 20th century; South Carolina; History; Political parties; Politics and government; South Carolina; dept.his; faculty_collection

The Hammer of the Inquisitors: Brother Bernard Délicieux and the Struggle Against the Inquisition in Fourteenth-Century France - Friedlander, Alan (Brill, 2000)
Keywords: Bernard; Délicieux; frère; approximately 1260-approximately 1320; Franciscans; Biography; Inquisition; Church history; France; Languedoc; Languedoc; Languedoc (France); dept.his; faculty_collection

A Narrative That Was Not Her Own: Mary I as Mediterranean Queen - Kern, Darcy (Writing Mary I: History, Historiography, and Fiction, 2022)
Nearly every biography of Mary Tudor mentions her acquisition of the Kingdom of Naples and the Spanish kingdoms through her marriage to Philip Habsburg, later Philip II of Spain, but they say little about her role as queen consort, primarily because she failed to control the narrative of her reign. She made little effort to patronize writers, disperse her symbols, send images of herself, use masculine terminology like her grandmother Isabel of Castile, or involve herself in the governance of her Mediterranean kingdoms. Her real and symbolic absence in the south, and the presence of Doña Juana, Philip’s sister and the capable regent of the Spanish kingdoms in his absence, led to her marginalization. This has had long-lasting consequences for the historiography of her reign, as historians have generally confined themselves to studying her in her English context using the gendered language of early Spanish writers while omitting her entirely from Naples.
Keywords: award_winner; dept.his

Competitive hagiography in biographies of al-Awzā'ī and Sufyān al-Thawrī - Judd, S.C. (Journal of the American Oriental Society, 2002)
The present paper examines how followers of 'Abd al-Rahcombining dot belowmān b. 'Amr al-Awzā'ī and Sufyān al-Thawrī tried to create boundaries between the nascent madhhabs that claimed them as eponyms. In the absence of significant differences in legal method, students turned to the two shaykhs' responses to the 'Abbāsid revolution to draw distinctions between them. The Arabic biographical sources contain stories of their responses to the revolution that reveal a dialogue between followers of the two shaykhs about the relative merits of their choices. The changing interpretations of their attitudes toward the 'Abbāsid regime and the exaggeration evident in the anecdotes examined have significant implications for our reading of medieval Arabic biographical sources.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his

From l'état, c'est moi to l'état, c'est l'état: Mapping in early modern France - Petto, C.M. (Cartographica, 2005)
Using the printed works of two French cartographers, Alexis-Hubert Jaillot and Guillaume Delisle, I investigate how the changing interests of the government directed not only the process of map-making but the rhetoric evident in printed maps and atlases. Jaillot, a commercial map publisher flourishing during the second half of the seventeenth century, produced maps that participated in the fabrication of the image of Louis XIV. Maps served this "cult of image" and contributed to a multimedia show to glorify the reign of the Sun King and to support his personal state - l'état, c'est moi. In the eighteenth century, while a rhetoric of image was still present on printed maps, the "cult of image" was dead and mapping appealed to the rise of the impersonal or bureaucratized state - l'état, c'est l'état. Delisle produced maps as instruments of statecraft that aided the state in furthering its domestic and international interests. In particular, printed maps of the Americas served the government's need to acquire greater territorial control. While images were still powerful on New World maps, the French boundary claims, egregious to some, if uncontested could be produced time and again as a true representation and legitimization of territorial control.
4 citations (Crossref) [2023-10-31]
Keywords: Cartography; France; History; Image; Louis XIV; Printed maps; Rhetoric; Scientific authority; dept.his; eighteenth century; historical cartography; mapping method; territorial delimitation

In defense of homology and history: A response to Allen - Paddock, T. (Philosophy and Geography, 2004)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

"I should not be wearing a pilgrim hat": Making an Indian place in urban schools, 1945-75 - Amerman, S. (American Indian Culture and Research Journal, 2007)
2 citations (Crossref) [2023-10-31]
Keywords: dept.his

Playing the feminine card: Women of the early modern map trade - Petto, C.M. (Cartographica, 2009)
Images of allegorical women have often appeared on maps or in atlas frontispieces as objects in need of security provided by male protectors or as the counterpoint, objects to be dominated by male possessors. Exploring the role of women in the early modern map trade initially reveals not only a similar male dominance but also similar calls for protection. Nearly 10 years ago, Alice Hudson and Mary McMichael Ritzlin produced a checklist of about 300 pre-twentieth-century women in cartography. The present work contributes to the further investigation of some of these women in the early modern map trade and studies in the allied field of book printing, and more general works on women in commercial trade provide the framework for this piece. Women in the map trade were quite cognizant of the challenges of their gender and used a feminine discourse-that is, they played the feminine card-when it served their interests. All of these women, however, participated in the male discourse of the corporate community, which entailed not only making contracts and partnerships and advertising and producing new works but also making use of the social network within the trade, as well as exploiting the patronage connections cultivated by their husbands before them.
5 citations (Crossref) [2023-10-31]
Keywords: Angleterre; England; France; commerce de l'impression des cartes; dept.his; engravers; femmes; graveurs; image; map publishers; map-printing trade; women; éditeurs cartographiques

The great industrial war: Framing class conflict in the media, 1865-1950 - Rondinone, T. (Rutgers University Press, 2009)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers.Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported. copyright © 2010 by Troy Rondinone All rights reserved.
Journal Abbreviation: The Gt. Indust. War: Framing Cl. Confl ict in the Media, 1865-1950 Pages: 247 Publication Title: The Gt. Indust. War: Framing Cl. Confl ict in the Media, 1865-1950
Keywords: dept.his

Reconstructing meaning in Deuteronomy 22:5: Gender, society, and transvestitism in Israel and the ancient Near East - Vedeler, H.T. (Journal of Biblical Literature, 2008)
4 citations (Crossref) [2023-10-31]
Keywords: dept.his

Sex, drink, and drugs: Tobacco in seventeenth-century Russia - Chrissidis, N.A. (Tobacco in Russian History and Culture: From the Seventeenth Century to the Present, 2011)
Journal Abbreviation: Tob. in Russian History and Culture: From the Seventeenth Century to the Present
Keywords: dept.his

Manufacturing Mohism in the Mencius - Radice, T. (Asian Philosophy, 2011)
The Mencius contains several negative remarks about the Mohists and their doctrine of 'universal love' (jian'ai). However, little attention has been paid to whether Mencius' descriptions of Mohism were accurate. Fortunately, there is a surviving record of the beliefs of Mozi in the text that bears his name. In this essay, I analyze this text and descriptions of Mohism from other early Chinese texts, and compare them to the criticisms of Mohism in the Mencius. Ultimately, I show that the image of the Mohists as ones who promoted a doctrine that contradicted filial piety was inaccurate, and obscured the complexities of filial piety in the Warring States period. © 2011 Taylor and Francis.
8 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Ella Grasso: Connecticut's pioneering governor - Purmont, J.E. (Wesleyan University Press, 2012)
When Ella Tambussi Grasso ran for governor of Connecticut in 1974, she had not lost an election since she was first voted into the state's General Assembly in 1952. The people of Connecticut chose her as the nation's first woman to be elected governor in her own right-the capstone of a long and successful career dedicated to public service, effective government, and the democratic process. During her tenure as governor, Grasso's leadership was tested in the face of fiscal problems, state layoffs, and budget shortfalls. The daughter of Italian immigrants, she endeared herself to her constituents during the great Blizzard of 1978, when she stayed at the State Armory around the clock to direct emergency operations and make frequent television appearances. Author Jon E. Purmont, who served as Grasso's executive assistant when she was governor, draws on his diary from that time, research in Grasso's archives, and interviews with Grasso's family and friends to give us a rich and intimate portrait of this political pioneer. © 2012 Jon E. Purmont. All rights reserved.
Journal Abbreviation: Ella Grasso: Connecticut's Pioneer. Gov. Pages: 264 Publication Title: Ella Grasso: Connecticut's Pioneer. Gov.
Keywords: dept.his

Would a saola by any other name still be a saola?: Appropriating rare animals, expropriating minority peoples - Thompson, C.M. (State, Society and the Market in Contemporary Vietnam: Property, Power and Values, 2012)
Journal Abbreviation: State, Society and the Market in Contemporary Vietnam: Property, Power and Values
Keywords: dept.his

Divergent paths: Processes of identity formation among German speakers, 1730-1760 - McDaniel, M.B. (A Peculiar Mixture: German-Language Cultures and Identities in Eighteenth-Century North America, 2013)
Journal Abbreviation: A Peculiar Mixture: German-Language Cultures and Identities in Eighteenth-Century N. Am.
Keywords: dept.his

Friday Night Fighter: Gaspar "Indio" Ortega and the Golden Age of Television Boxing - Rondinone, Troy (University of Illinois Press, 2013)
Friday Night Fighter relives a lost moment in American postwar history, when boxing ruled as one of the nation's most widely televised sports. During the 1950s and 1960s, viewers tuned in weekly, sometimes even daily, to watch widely-recognized fighters engage in primordial battle, with the Gillette Cavalcade of Sports Friday Night Fights being the most popular fight show. Troy Rondinone follows the dual narratives of the Friday Night Fights show and the individual story of Gaspar "Indio" Ortega, a boxer who appeared on primetime network television more than almost any other boxer in history. From humble beginnings growing up poor in Tijuana, Mexico, Ortega personified the phenomenon of postwar boxing at its greatest, appearing before audiences of millions to battle the biggest names of the time, such as Carmen Basilio, Tony DeMarco, Chico Vejar, Benny "Kid" Paret, Emile Griffith, Kid Gavilan, Florentino Fernández, and Luis Manuel Rodriguez.–(Source of description unspecified.)
Keywords: Hispanic Americans; History; History; Boxing; History; Television broadcasting of sports; Ortega; Gaspar "Indio"; 1935-; Boxing; United States; United States; Sports; dept.his; faculty_collection

Greeks in seventeenth-century Russia - Chrissidis, N.A. (Portraits of Old Russia: Imagined Lives of Ordinary People, 1300-1745, 2015)
Journal Abbreviation: Portraits of Old Russ.: Imagined Lives of Ordinary People, 1300-1745
Keywords: dept.his

Soul sister journey: Essence magazine and travel columns during the “me” decad - Carter-David, S. (Women's Magazines in Print and New Media, 2016)
Journal Abbreviation: Women's Magazines in Print and New Media
Keywords: dept.his

Were the umayyad-era qadarites Kāfirs? - Judd, S. (Islam. Hist. Civiliz., 2016)
Journal Abbreviation: Islam. Hist. Civiliz.
Keywords: dept.his

Platonic words: Paolo sarpi and roberto bellarmino as translators in the venetian interdict crisis - Kern, D. (Philological Quarterly, 2016)
Keywords: dept.his; ⛔ No DOI found

To know the distance: Wayfinding and roadmaps of early modern England and France - Petto, C.M. (Cartographica, 2016)
In 1675, John Ogilby produced his road atlas with strip maps which not only arrived with fanfare, but spawned several more publications that aimed to be user-friendly. As with many maps and atlases from the London printing trade, the objectives were to serve consumers, acquire a piece of the market, and have an outlet for a new edition. Across the Channel, however, the road network of France, as with other public works, was not only state-directed but a tool of state power. Not until nearly one hundred years later did Claude-Sidoine Michel and Louis-Charles Desnos produce L'Indicateur Fidele, which provided strip maps for merchants, navigators, and travelers. This publication emerged out of the French national mapping project directed by the Cassini family. In the interim, while French map makers produced maps with an appeal to serving the state, they, like their London contemporaries, also hoped to maintain a thriving business and attract an audience, often through the traditional French social institution of patronage. The purpose of this comparative study of (post) road maps and atlases of England and France is to investigate the role of the government and the publishing trade in the production of these works. © 2016 University of Toronto Press.
2 citations (Crossref) [2023-10-31]
Keywords: Consumers; England; France; London [England]; Map trade; Patronage; Post roads; Strip maps; United Kingdom; cartography; dept.his; mapping

Thou uncracked keel: The many voyages of the Whaleship Charles W. Morgan and the presence of the American Maritime past - Smith, J.W. (New England Quarterly-A Historical Review of New England Life and Letters, 2016)
The ship wherein Theseus and the youth of Athens returned from Crete had thirty oars, and was preserved by the Athenians down even to the time of Demetrius Phalereus, for they took away the old planks as they decayed, putting in new and stronger timber in their place, in so much that this ship became a standing example among the philosophers, for the logical question of things that grow; one side holding that the ship remained the same, and the other contending that it was not the same. © 2016 by The New England Quarterly. All rights reserved.
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

The lands of orthodoxy in the seventeenth century circa 1590-1720 - Bushkovitch, P.; Chrissidis, N.A.; Pǎun, R.G. (Cahiers du Monde Russe, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

Signum meum apposui: Notaries and their signs in medieval languedoc - Friedlander, A. (The Experience of Power in Medieval Europe, 950-1350, 2017)
Journal Abbreviation: The Exp. of Power in Mediev. Eur., 950-1350
Keywords: dept.his

To the editors - Forbes, R.P.; Mintz, S.; Stauffer, J. (American Historical Review, 2019)
Keywords: dept.his; ⛔ No DOI found

Intellectuals and “democratic elements”: A distrusted underclass - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
As the targets of numerous campaigns, intellectuals have sustained mental torment and physical suffering on a large scale. Like the deprivation of human rights for biological and genetic reasons in other lands or other ages, Chinese intellectuals were destined to suffer abridgement of their human rights in the People’s Republic of China for political and ideological reasons. The term “intellectuals” refers to all those who have had a middle school/higher education and those with similar educational levels. Included in the ranks of intellectuals were members of the so-called democratic parties. These people, never large in number, were mostly well educated and well known in intellectual circles. The Cultural Revolution will be long remembered by intellectuals not only as a period of continued mental torment from the earlier days, but more particularly as a period of the most cruel physical abuses in human history. Intellectuals, deprived of their most precious human rights, continue to exist in mainland China as an underclass. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his

Red guards and political dissidents (I): Tools of violence and power struggle - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
In 1966, Mao Zedong launched the Great Proletarian Cultural Revolution in a last attempt to remake China in his image. He believed that the country was led by a party infested from the top on down with “capitalist-roaders” who had betrayed the proletarian goals of true socialism by following the bourgeois line. Denied support in the power structure, Mao sought help from the outside, mobilizing millions of high school and college students as the “Red Guards” to strike down his enemy in an unprecedented campaign that left the nation nearly paralyzed. Red Guard organizations of confusing ideological persuasions soon proliferated throughout the country, and the whole movement quickly got out of control and degenerated into total chaos. That the Red Guards were used by Mao as a tool in the ideologically based power struggle within the party is not only the consensus of most observers but also has been freely admitted by many former Red Guards. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his

Red guards and political dissidents (II): Victims beyond a generation - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
Many former Red Guards who through the Cultural Revolution were encouraged to participate in unrestrained violence, saw the seamy side of the regime as a result and were themselves eventually suppressed and reached the conclusion that the system was corrupt and had to be changed. Former Red Guards who turned political activists varied greatly in their often vaguely defined outlooks and their intensity of commitment and activity. Wei Jingsheng, China’s most celebrated Red Guard-turned dissident, related a similar experience in an unfinished autobiographical account written before his arrest and smuggled out of the country in 1980. Many former Red Guards understandably see a silver lining in the destructive rampage they committed during the height of the Cultural Revolution. The Red Guard movement has come full circle. The human rights tragedy of the movement is threefold. In the first stage, the Red Guards were Mao’s “little generals” trampling on the human rights of their victims. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his

Prime (and crime) time: Boxing in the 1950s - Rondinone, T. (The Camb. Companion to Box., 2019)
Journal Abbreviation: The Camb. Companion to Box.
Keywords: dept.his

Human rights in the people’s republic of China - Wu, Y.-L.; Michael, F.; Copper, J.F.; Lee, T.-L.; Chang, M.H.; Gregor, A.J. (Taylor and Francis, 2019)
This book examines the effects that political institutions, the legal system, and economic policies have had on the human rights record in the PRC since 1949. The authors first address the problems of assessing political liberties in a nation that emphasizes economic over civil rights and that has traditionally valued collective rights over individ. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China Pages: 332 Publication Title: Hum. Rights in the People's Repub. of China
Keywords: dept.his

A dramaturgy of death: Performing (and spectating) filial piety in early china - Radice, T. (Journal of Chinese History, 2022)
This essay analyzes the early Chinese elite discourse on filial death rituals, arguing that early Chinese texts depict these rituals as performance events. Building on spectacle of xiao sacrifices in the Western Zhou Dynasty, Eastern Zhou authors conceived of filial death rituals as dramaturgical phenomena that underscored not only what needed to be performed, but also how it should be performed, and led to an important distinction between personal dispositions and inherited ritual protocol. This distinction, then, led to concerns about artifice in human behavior, both inside and outside the Ruist (Confucian) tradition. By end of the Warring States Period and in the early Western Han Dynasty, with the embracement of artifice in self-cultivation, the dramatic role of the filial son in death rituals became even more developed and complex, requiring the role of cultivated spectators to be engaged critics who recognized the nuances of cultivated performances. Copyright © The Author(s), 2021. Published by Cambridge University Press.
0 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85118183872
Keywords: dept.his; peer-reviewed

Book Review: The keepers of the seas the blue age gregg easterbrook PublicAffairs, 2021. 304 pp. - Smith, Jason W. (Science (New York, N.Y.), 2021)
0 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pubmed/34516783
Keywords: article; book.review; dept.his

Understanding the role of wrongdoing in technological disasters: Utilizing ecofeminist philosophy to examine commemoration. - Roe, Sarah M.; Zavar, Elyse (Studies in history and philosophy of science, 2021)
Stemming from human accident, error, or neglect, technological disasters, such as chemical spills, toxic waste contamination, nuclear radiation, transportation accidents, and factory explosions, are products of the modern industrial complex. Toxic contamination of the land can permanently displace people from their homes and erase places from the landscape. Commemoration provides an opportunity to remember the past and celebrate culturally significant place attachments while contributing to the recovery process by aiding in community healing after devastating events. We focus on two key components regarding commemoration after technological disaster, namely the acknowledgement of wrongdoing and the celebration of a resilient population and landscape. We argue that a combination of ecofeminist philosophy and environmental justice frameworks allows for a better understanding of the cycle of disaster and mitigation as it pertains to targeted groups, and that commemorative acts and artifacts following human-made disasters often fail to successfully reform this cycle. Moreover, the combination of ecofeminist philosophy and environmental justice allows us to examine the complex relationship between responsibility and targeted groups through disaster commemoration, which serves as an important way to communicate wrongdoing to both the local and greater population. Through engagement with ecofeminist philosophy and environmental justice frameworks, we explicate how commemoration after technological disaster can disrupt or reinforce systematic inequalities. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31] http://www.ncbi.nlm.nih.gov/pubmed/34111819 ; https://europepmc.org/article/MED/34111819 ; https://philpapers.org/rec/ROEUTR ; https://www.ncbi.nlm.nih.gov/pubmed/34111819
Keywords: article; artifact; contamination; dept.his; disaster; explosion; factory; human; justice; neglect; peer-reviewed; philosophy; responsibility; toxic waste

Bridges: Technology and the Social - Paddock, Troy R. E. (Environment, Space, Place, 2010)
1 citations (Crossref) [2023-10-31]
Keywords: dept.his

“No Man’s Land”: Forbidden and Subversive Space in War - Paddock, Troy R. E. (Environment, Space, Place, 2013)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

Spatial relations and the struggle for space: Friedrich Ratzel’s impact on German education from the Wilhelmine Empire to the Third Reich - Paddock, Troy (Journal of Educational Media, Memory, and Society, 2016)
This article examines the influence of Friedrich Ratzel’s idea of the struggle for space and its impact on cultural and national development depicted in German geography and history textbooks from the Wilhelmine era to the Third Reich. Ratzel’s concept of bio-geography conceived the state as a living organism that is the product of humanity’s interaction with the land and also facilitates humanity’s spread across the earth. German textbooks promoted a similar concept of the state in their portrayal of geography and history, the implications of which were appropriated by the National Socialists to support their geopolitical goals.
3 citations (Crossref) [2023-10-31]
Keywords: Education; Friedrich ratzel; Geography instruction; History instruction; National identity; State; Textbooks; dept.his

Land makes the man: topography and national character in german school books - Paddock, Troy R. E. (Lived topographies and their mediational forces, 2005)
"This collection explores the various forms of narrative, semiotic, and technological mediation that shape the experience of place. From the East End of London to Navajo lands to Ground Zero, Lived Topographies examines the great effect of language, mass media, surveillance, and other incursions of the contemporary world on topographical experience and description. Gary Backhaus and John Murungi have assembled a wide array of scholars to provide an interdisciplinary approach to this subject, giving this collection a unique perspective on the phenomenology of place."–Jacket.
OCLC: 57557650
Keywords: dept.his

Chronoscapes/chronos escapes: a meditation on historical time - Paddock, Troy R. E. (Ecoscapes: geographical patternings of relations, 2006)
OCLC: 62493042
Keywords: dept.his

Is one world enough for all of us?: Thoughts on globalization - Paddock, Troy R. E. (Dangers in the incommensurability of globalization: socio-political volatilities, 2008)
OCLC: 1062216027
Keywords: dept.his

A Call to Arms: Propaganda, Public Opinion, and Newspapers in the Great War - Paddock, Troy R. E. (Praeger Publishers, 2004)
World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t., World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t
Keywords: Press coverage; Propaganda; World War; 1914-1918; Public opinion; Press and propaganda; War; World War; 1914-1918; dept.his; faculty_collection

Creating the Russian Peril: Education, the Public Sphere, and National Identity in Imperial Germany, 1890-1914 - Paddock, Troy R. E. (Camden House, 2010)
German attitudes toward and stereotypes of Russia before the First World War and how they were inculcated in the public.
SCSU Faculty Scholar Award
Keywords: 1871-1918; 19th century; Education; 19th century; Nationalism; 20th century; Germany; 20th century; Nationalism; Foreign public opinion; German; Russia; Germany; Germany; Germany; Germany; Russia; History; History; Education; Political aspects; Press coverage; Public opinion; Relations; Russia; Russia; SCSU Faculty Scholar Award; award_winner; dept.his; faculty_collection

World War I and Propaganda - Paddock, Troy R. E. (Brill, 2014)
World War I and Propaganda offers a new look at a familiar subject. The contributions to this volume demonstrate that the traditional view of propaganda as top-down manipulation is no longer plausible. Drawing from a variety of sources, scholars examine the complex negotiations involved in propaganda within the British Empire, in occupied territories, in neutral nations, and how war should be conducted. Propaganda was tailored to meet local circumstances and integrated into a larger narrative in which the war was not always the most important issue. Issues centering on local politics, national identity, preservation of tradition, or hopes of a brighter future all played a role in different forms of propaganda. Contributors are Christopher Barthel, Donata Blobaum, Robert Blobaum, Mourad Djebabla, Christopher Fischer, Andrew T. Jarboe, Elli Lemonidou, David Monger, Javier Pounce,Catriona Pennell, Anne Samson, Richard Smith, Kenneth Andrew Steuer, María Inés Tato, and Lisa Todd.
Publication Title: World War I and Propaganda
Keywords: dept.his

Notes on the state of Virginia: an annotated edition - Jefferson, Thomas; Forbes, Robert Pierce (Yale University Press, 2021)
Keywords: Description and travel; Early works to 1800; Early works to 1800; Virginia; History; Virginia; dept.his; faculty_collection

'Truth Systematised’: The Changing Debate over Slavery and Abolition - Forbes, Robert P. (Prophets of Protest: Reconsidering the History of American Abolitionism, 2006)
The first collection of original contributions on American abolitionism to appear in a generation.The campaign to abolish slavery in the United States was the most powerful and effective social movement of the nineteenth century and has served as a recurring source of inspiration for every subsequent struggle against injustice. But the abolitionist story has traditionally focused on the evangelical impulses of white, male, middle-class reformers, obscuring the contributions of many African Americans, women, and others.Prophets of Protest, the first collection of writings on abolitionism in more than a generation, draws on an immense new body of research in African American studies, literature, art history, film, law, women's studies, and other disciplines. The book incorporates new thinking on such topics as the role of early black newspapers, anti-slavery poetry, and abolitionists in film and provides new perspectives on familiar figures such as Sojourner Truth, Louisa May Alcott, Frederick Douglass, and John Brown.With contributions from the leading scholars in the field, Prophets of Protest is a long overdue update of one of the central reform movements in America's history.
Keywords: dept.his

The Missouri Controversy and Sectionalism - Forbes, Robert P. (Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson, 2008)
In 1815 the United States was a proud and confident nation. Its second war with England had come to a successful conclusion, and Americans seemed united as never before. The collapse of the Federalist party left the Jeffersonian Republicans in control of virtually all important governmental offices. This period of harmony—what historians once called the Era of Good Feeling—was not illusory, but it was far from stable. One-party government could not persist for long in a vibrant democracy full of ambitious politicians, and sectional harmony was possible only as long as no one addressed the hard issues: slavery, race, western expansion, and economic development.Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson inaugurates a new series for the United States Capitol Historical Society, one that will focus on issues that led to the secession crisis and the Civil War. This first volume examines controversies surrounding sectionalism and the rise of Jacksonian Democracy, placing these sources of conflict in the context of congressional action in the 1820s and 1830s. The essays in this volume consider the plight of American Indians, sectional strife over banking and commerce, emerging issues involving slavery, and the very nature of American democracy.“It is to be regretted that the rich and powerful too often bend the acts of government to their selfish purposes…. There are no necessary evils in government. Its evils exist only in its abuses. If it would confine itself to equal protection, and, as Heaven does its rains, shower its favors alike on the high and the low, the rich and the poor, it would be an unqualified blessing. In the act before me there seems to be a wide and unnecessary departure from these just principles.”—Andrew Jackson, Veto Message Regarding the Bank of the United States, July 10, 1832“I consider, then, the power to annul a law of the United States, assumed by one State, incompatible with the existence of the Union, contradicted expressly by the letter of the Constitution, unauthorized by its spirit, inconsistent with every principle on which it was founded, and destructive of the great object for which it was formed.”—Andrew Jackson, Proclamation Regarding Nullification to the People of South Carolina, December 10, 1832
Keywords: dept.his

The russian holy synod and the greeks: Reconsidering greek-russian relations in the early modern period (16th–18th centuries) - Chrissidis, Nikolaos A. (Canadian-American Slavic Studies, 2020)
The article first surveys Greek interpretations of the creation of the Russian Holy Synod by Peter the Great. It provides a critical assessment of the historiographical paradigm offered by N.F. Kapterev for the analysis of Greek-Russian relations in the early modern period. Finally, it proposes that scholars should focus on a Greek history of Greek-Russian relations as a complement and possibly corrective to the Kapterev paradigm. © verlag ferdinand schöningh, 2020.
1 citations (Crossref) [2023-10-31] tex.ids: chrissidisRussianHolySynod2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092349515 type: Article
Keywords: Aleksander stourdza; Greek-russian relations; Konstantin oinonomos; Nikolai kapterev; Peter the great; Russian holy synod; dept.his; peer-reviewed

The venomous course of southwestern opium: Qing prohibition in Yunnan, Sichuan, and Guizhou in the early nineteenth century - Bello, David (The Journal of Asian Studies, 2003)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-511-721-924-233 tex.type: [object Object]
Keywords: dept.his

Gedachtes wohnen: Heidegger and cultural geography - Paddock, Troy (Philosophy & Geography, 2004)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-707-720-981-012 tex.type: [object Object]
Keywords: cultural geography; dept.his

The historiography of american violence - Leonard, Ira M; Leonard, Christopher C (Homicide Studies, 2003)
Historians have generally agreed that the United States has always been an extremely violent nation; however, since the 1950s they have been myopic in their treatment of violence in America and have not provided the American people with essential information about their society and culture. Those historians who focused on violence in America, until the 1990s, have focused on only one form of violence—collective social violence. Largely overlooked, and equally significant, are interpersonal violence (including criminal and domestic violence) and the effect of war. This deficiency helps explain why Americans seem genuinely at a loss to understand the nature, character, and frequency of violence in America's past and present, especially when a high-profile violent incident occurs. This article surveys the historiography of violence in America through the 1990s and examines the contributions of historians and legal scholars who have focused on interpersonal and criminal violence. © 2003, SAGE Publications. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/168-886-742-543-29X tex.type: [object Object]
Keywords: dept.his; historiography; lynching; riots; vigilantism

The pennsylvania state equal rights league and the northern black struggle for legal equality, 1864-1877 - Davis, Hugh (Pennsylvania Magazine of History and Biography, 2002)
Citation Key Alias: lens.org/021-378-663-485-819 tex.type: [object Object]
Keywords: dept.his; ⛔ No DOI found

Out of Africa - Feinberg, H.M.; Solodow, J.B. (Journal of African History, 2002)
This article traces the origins of the familiar quotation, 'there is always something new coming out of Africa'. It demonstrates that the phrase was a proverb that originated in Greece no later than the fourth century BC. It charts the transmission of the phrase from Aristotle to the twentieth century, noting that Erasmus is the most important link in the Renaissance and that he may be responsible for the current form in which the phrase is used. The article also shows that the meaning of the phrase was very different in ancient times from what it is today. Whereas 'something new' to Aristotle meant strange hybrid animals, current writers use the phrase with a sense of admiration.
9 citations (Crossref) [2023-10-31]
Keywords: Africa; Historiography; dept.his; dept.wll; history; perception; regional geography

South African territorial segregation: new data on African farm purchases, 1913-1936 - Feinberg, Harvey M; Horn, Andre C (The Journal of African History, 2009)
By using new sources and a complementary historical and geo-analytical approach, this article Illustrates that the Natives Land Act (no. 27 of 1913) failed to stop Africans from buying land. New evidence demonstrates that African land ownership outside the reserves in the Transvaal actually increased after 1913. This evidence leads to a deeper questioning of the extent to which the South African government was able to impose rural territorial segregation by 1936 and reveals the limits of white power in the early Union period.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-862-260-598-682 tex.type: [object Object]
Keywords: Archives; Land; Law; Race; South Africa; apartheid; dept.his; historical geography; land tenure; landownership; legislation; racial segregation

Semblance of Sovereignty: Cartographic Possession in Map Cartouches and Atlas Frontispieces of Early Modern Europe - Petto, Christine M. (Symbolic Landscapes, 2009)
Maps always present an interpretation of reality and always carry distortions, some of which are consciously or unconsciously ideological. The geographicity of mapping, which involves an intertwining of both science and art, is a vehicle for spatialized/spatializing interpretations of an actual spatiality, and as such is a catalyst for enacting further spatial productions on the basis of the capacity of maps to project themselves “into the landscape.” The scientific pretensions of mapping serve to veil the character of their projective enactment. Maps always entail virtual embodiment, that is, maps realize one possibility out of many, even in the most mathematically “accurate” of spatial relations. Thus, if the imaginative involves both embodied schema and virtual embodiments, we cannot dismiss the role of the geography of imagination in a dialectical relation with the geography of perception, of the actual. The symbolic function of cartouches and frontispieces provides an imagineering context of constructing reality on the basis of the symbolization.
Citation Key Alias: lens.org/078-762-124-744-708
Keywords: Facsimile Edition; Manuscript Library; Online Collection; United Province; Virtual Embodiment; dept.his

Guarding the switch: cultivating nationalism during the pullman strike - Rondinone, Troy (The Journal of the Gilded Age and Progressive Era, 2009)
The Pullman Strike of 1894 was a cataclysmic event for the nation. During its violent course, the print media provided an interpretive frame that portrayed the strike in large measure as an immigrant-inspired attack on American laws and democratic customs. Often characterizing the strikers as “foreigners” in the thrall of anarchist ideologies and a tyrannous labor chieftain, journalists painted a stark picture indeed. Employing framing theory, Gramsci's notion of hegemony, and recent insights on the ethnic quality of nationalism, this essay argues that newspapers and other major print periodicals significantly contributed to the formation of nationalist attitudes at a time when many Americans were deeply worried over the direction in which the country was headed. © 2009, Society for Historians of the Gilded Age and Progressive Era. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/091-980-600-754-189 tex.type: [object Object]
Keywords: dept.his

Captured on the gold coast: “Illegal” enslavement, freedom and the pursuit of justice in dutch courts, 1746–1750 - de Kok, Gerhard; Feinberg, Harvey M. (Journal of Global Slavery, 2016)
In May of 1746, slaving captain Christiaan Hagerop illegally captured ten Gold Coast canoe paddlers, seven of whom were free Africans from Elmina and Fante. Hagerop subsequently sailed to Suriname, where he sold the paddlers into slavery. To appease the relatives of the captured men and to safeguard its reputation among local Africans, the Dutch West India Company (WIC) launched a search for the kidnapped paddlers. Six of the men were eventually located in Suriname in 1749, the seventh having died in slavery. While the Africans were transported back to the Gold Coast via Amsterdam, the WIC tried to have Hagerop extradited to its Gold Coast possessions to receive punishment for his crime. A legal battle over jurisdictional competence ensued in the Dutch Republic, the outcome of which was that the captain was made to stand trial in Amsterdam, but in the end he received very little punishment. © 2016 Copyright 2016 by Koninklijke Brill NV, Leiden, The Netherlands.
0 citations (Crossref) [2023-10-31]
Keywords: Africa; Gold Coast; Slave Trade; Suriname; dept.his; wic

The World of Eastern Orthodoxy - Chrissidis, Nikolaos A. (The Oxford Handbook of Early Modern European History, 1350-1750, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Citation Key Alias: lens.org/025-896-017-121-207
Keywords: dept.his

The early qadariyya - Judd, Steven C. (The Oxford Handbook of Islamic Theology, 2014)
This article discusses the briefly significant Qadariyya movement during the Umayyad period, with an emphasis on how the movement and its adherents were treated in later sources. The article examines the doctrine of human free will advocated by the Qadariyya, exploring the impetus behind their theological viewpoints and the doctrinal complications that accompanied human free will. It also addresses the debate about the origins of both the doctrine and the movement, and the significance of accusations of Christian roots. The article discusses the views ascribed to prominent Qadari leaders, including Maʿbad al-Juhanī and Ghaylān al-Dimashqī, as well as the systematic persecution of the Qadariyya, led by al-Awzāʿī. It also examines the politicization of the Qadariyya and their entanglement with Yazīd (III) b. al-Walīd’s rebellion during the third fitna. Finally, the article addresses the eclipse of the Qadariyya by the Muʿtazilites.
Keywords: dept.his

Religious Scholars and the Umayyads: Piety-Minded Supporters of the Marwānid Caliphate - Judd, Steven C. (Routledge, 2014)
SCSU Faculty Scholar Award
Keywords: Doctrines; History; Judges (Islamic law); History; Muslim scholars; Islamic law; SCSU Faculty Scholar Award; Umayyad dynasty; Islam; award_winner; dept.his; faculty_collection

Muslim Persecution of Heretics during the Marwānid Period (64–132/684–750) - Judd, Steven (Al-Masaq: Journal of the Medieval Mediterranean, 2011)
This article traces the emergence of a systematic approach to combating heresy during the Umayyad period. It argues that the Umayyads sought to silence religious dissent by labelling it as heresy and that the doctrinal boundaries of orthodoxy narrowed as the Umayyad period progressed. The article also asserts that Umayyad efforts to impose their vision of orthodoxy were an important precedent for the mihna under the Abbasids. © 2011 Society for the Medieval Mediterranean.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/146-546-256-080-649 tex.type: [object Object]
Keywords: Abd al-Malik; Ghaylan al-Dimashqi; Heretic; Hisham; Islam - heresy; Islamic scholar; Mabad al-Juhani; Qadariyya; Theological movement; Ummayad caliph; Ummayad caliphate; dept.his

The persistence of republicanism: class war talk, american style - Cassano, Graham; Rondinone, Troy (Labor Studies Journal, 2010)
The authors argue that there have been moments in American history when a class analysis entered into popular discourse. What has been "exceptional" about American history is the manner in which that class analysis emerged. When Americans speak the language of "class" and "class warfare," it is often clothed in the rhetoric of labor republicanism. That is, rather than offering a systemic analysis of capitalist processes, American labor republicanism offers a class analysis that sets a small set of bad acting "elites" and their dependents against the mass of American workers. The authors trace this discourse from Franklin Roosevelt's 1936 description of "economic royalists" to Lou Dobbs's nativist attack on "corporate elites" and undocumented workers. As the United States enters a new period of "class awareness" and economic crisis, this republicanism returns to haunt public discourse. © 2010 UALE.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/092-482-651-700-468 tex.type: [object Object]
Keywords: Franklin D. Roosevelt; Lou Dobbs; Marxian analysis; class warfare; dept.his; labor republicanism

Sinification as Limitation: Minh Mạng’s Prohibition on Use of Nôm and the Resulting Marginalization of Nôm Medical Texts - Thompson, C. Michele (Looking at it from Asia: the Processes that Shaped the Sources of History of Science, 2010)
For Vietnamese scholars in the late eighteenth and early nineteenth centuries reading and writing ability in both Chinese and Nôm (an ideographic writing system used to write Vietnamese) was considered an essential tool of scholarship and literary expression.
Citation Key Alias: lens.org/016-294-392-174-12X
Keywords: Chinese Character; Imperial Examination System; Medical Text; Royal Court; Vietnamese Language; dept.his

The Folklore of Deinstitutionalization: Popular Film and the Death of the Asylum, 1973–1979 - Rondinone, Troy (Journal of American Studies, 2019)
The demise of America's state mental hospital system, or “deinstitutionalization,” has received much attention from sociologists and historians of medicine. Less understood is the manner in which the public experienced and came to terms with it. Using elements of folklore and horror studies, I will examine how popular films accommodated audiences to institutional decline and confirmed popular antistatist pessimism. The Exorcist (1973), One Flew over the Cuckoo's Nest (1975), Halloween (1978), and When a Stranger Calls (1979) helped weave a tapestry of distrust. By endorsing popular conceptions of institutional failure and presenting mythical narratives of individualist triumph, these films helped pave a path towards the conservative Reagan era to come.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Lovecraft Meets the Mummy: Orientalism, Race, and Monstrous Egypt in “Imprisoned with the haraohs” and “Out of the Aeons” - Rondinone, Troy (Lovecraftian Proceedings No. 3., 2019)
OCLC: 1112383993
Keywords: dept.his; faculty_collection

The unforgettable age: young in Costa Rica of XX century - Coury Kordick, Carmen Coury (Americas, 2019)
0 citations (Crossref) [2023-10-31] tex.address: 32 AVENUE OF THE AMERICAS, NEW YORK, NY 10013-2473 USA tex.affiliation: Kordick, C (Reprint Author), Southern Connecticut State Univ, New Haven, CT 06515 USA. Kordick, Carmen, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: carmen.kordick@gmail.com tex.da: 2019-10-31 tex.doc-delivery-number: JB8QB tex.eissn: 1533-6247 tex.journal-iso: Americas tex.number-of-cited-references: 1 tex.publisher: CAMBRIDGE UNIV PRESS tex.research-areas: History tex.times-cited: 0 tex.type: Book review tex.unique-id: ISI:000488837000030 tex.usage-count-last-180-days: 0 tex.usage-count-since-2013: 0 tex.web-of-science-categories: History
Keywords: dept.his; peer-reviewed

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge, 2019)
Contesting the Origins of the First World War challenges the Anglophone emphasis on Germany as bearing the primary responsibility in causing the conflict and instead builds upon new perspectives to reconsider the roles of the other Great Powers. Using the work of Terrance Zuber, Sean McMeekin, and Stefan Schmidt as building blocks, this book reassesses the origins of the First World War and offers an explanation as to why this reassessment did not come about earlier. Troy R.E. Paddock argues that historians need to redraw the historiographical map that has charted the origins of the war. His analysis creates a more balanced view of German actions by also noting the actions and inaction of other nations. Recent works about the roles of the five Great Powers involved in the events leading up to the war are considered, and Paddock concludes that Germany does not bear the primary responsibility. This book provides a unique historiographical analysis of key texts published on the origins of the First World War, and its narrative encourages students to engage with and challenge historical perspectives.
Keywords: dept.his

‘Mixt marriages’: Ethnic and religious intermarriage among German-speakers in eighteenth-century Pennsylvania - McDaniel, Marie Basile (The History of the Family, 2019)
Civil and religious authorities in eighteenth-century America grew increasingly concerned over the freedom with which young people chose their marriage partners. Correlating racial, religious and cultural similarity in marriage to a stable society, these authorities attempted to limit marriage and sexual choices by requiring parental authority for marriage, distributing permits to a select few to perform marriages, and criminalizing racial miscegenation. Eighteenth-century Pennsylvania German authorities supported this attitude because they associated ethnic and religious out-marriage with the weakening of the body and the destruction of society. My study uses the marriage and birth records of eighteenth-century Pennsylvania Germans to examine their marriage and sexual relationships. I discovered that Pennsylvania Germans overwhelmingly chose to marry other German-speakers, out of proportion with their population. By examining the then available works on marriage and procreation, I discovered that Pennsylvania Germans read works that emphasized the necessity and importance of intra-ethnic and religious sex and marriage for the health of their children. Pennsylvania Germans chose their marriage partners in alignment with their community’s attitudes towards those of other ethnicities and religions. A small data set further suggests that relationships with non-Germans occurred but rarely became formalized. This complicates what we know about the sexual and emotional revolutions in the seventeenth and eighteenth centuries; far from a linear progression of attitudes towards sex, marriage, and others, eighteenth-century Pennsylvania Germans expressed multiple, contextually-driven perspectives, and in the process they created and maintained strong ethnic communities. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-122-575-243-949, pop00292 tex.type: [object Object]
Keywords: Defoe; German (citizen); German-speakers; Marriage; Pennsylvania; article; child; colonial; dept.his; destruction; ethnicity; female; human; human experiment; male; marriage; peer-reviewed; pre-marital; religion

Roman exempla in the early Tudor period - Kern, Darcy (English: Journal of the English Association, 2019)
Abstract. Roman exempla, or moralizing anecdotes, appear frequently in the English literature of the early Tudor period. Textual, authorial, and historical exe
0 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Empire by invitation: William Walker and manifest destiny in Central America - Coury Kordick, Carmen (Americas, 2019)
1 citations (Crossref) [2023-10-31] tex.address: 32 AVENUE OF THE AMERICAS, NEW YORK, NY 10013-2473 USA tex.affiliation: Kordick, C (Reprint Author), Southern Connecticut State Univ, New Haven, CT 06515 USA. Kordick, Carmen, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: carmen.kordick@gmail.com tex.da: 2019-10-31 tex.doc-delivery-number: HQ9TB tex.eissn: 1533-6247 tex.journal-iso: Americas tex.number-of-cited-references: 1 tex.publisher: CAMBRIDGE UNIV PRESS tex.research-areas: History tex.times-cited: 0 tex.type: Book review tex.unique-id: ISI:000462769300017 tex.usage-count-last-180-days: 0 tex.usage-count-since-2013: 0 tex.web-of-science-categories: History
Keywords: book.review; dept.his; peer-reviewed

Boxing in the ancient world - Nakamura, Byron J. (The Cambridge Companion to Boxing, 2019)
Keywords: dept.his

Beyond borders: Jean Gerson’s conciliarism in fifteenth-century Spain - Kern, Darcy (Renaissance and Reformation, 2019)
In recent years there has been renewed interest in conciliarism, the belief that the authority of the universal church resides in an ecumenical council, not the pope, though the perception remains that conciliarism had a negligible impact in Iberia. One way to better understand the evolution of conciliar thought in the Spanish kingdoms is by looking at the circulation of the works and ideas of the French conciliarist Jean Gerson (1363–1429). Though a complete reconstruction of Gerson’s circulation is impossible, one can offer an initial overview of his impact in the Spanish kingdoms not simply by counting manuscripts or incunabula, as valuable as that is, but by thinking broadly about networks of exchange and dissemination. Gerson’s works came to Spain through the church councils, trans-Pyrenees Carthusian networks, monastic reformers, printers and printing houses, mendicant reformers, and the library of the University of Salamanca. © 2019, (publisher Name). All Rights Reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Rolf Brandt and a conservative literary journalism - Paddock, Troy RE (Literary Journalism Studies, 2019)
Rolf Brandt (1886-1953) was a German journalist, author, and political commentator. His first work was as a war reporter on the Eastern Front during the opening months of the Great War (World War I). His reports appeared in several important German newspapers (Norddeutsche Allgemeine Zeitung and Frankfurter Zeitung) and were compiled and published in 1915 as Fünf Monate an der Ostfront: Kriegsberichte (Five months on the Eastern Front: War reports). Brandt's reports were more than just army-approved press releases. He wrote in a way that constructed a bridge between the home front and the front lines. In the process he employed techniques now associated with literary journalism. With a clear point of view, he told his story through a sequence of scenes, instead of a simple historical narrative, and included genuine dialogue and status details. While scholars of German literary journalism point to Egon Erwin Kisch as the originator of German literary journalism, this study suggests Brandt should be considered an early practitioner of literary journalism in the German language. More interestingly, Brandt's particular brand of literary journalism had an unmistakably conservative nationalist perspective, thus suggesting that it is possible to have a conservative form of literary journalism. © 2019 Literary Journalism Studies. All Rights Reserved.
Keywords: Conservative literary journalism; Germany; Propaganda; Rolf Brandt; Russia; World War I; dept.his; peer-reviewed; ⛔ No DOI found

Focus introduction: Swarms, herds, and peoples—examinations of interspecies dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
As its title suggests, this Focus draws our attention to the shift in perspective brought about by environmental history, compared to the more traditional approaches of history of science. Here human knowledge of and interaction with animals are understood as part of a historically variable system that encompasses both the human realm and its environment, a system in which the various components interact and shape each other dynamically.
Citation Key Alias: lens.org/130-110-172-036-255, pop00336 tex.type: [object Object]
Keywords: dept.his; peer-reviewed; ⛔ No DOI found

Welcoming ruin: The Civil Rights Act of 1875 - Friedlander, Alan; Gerber, Richard Allan (Brill, 2018)
Keywords: dept.his

Edification through the memory of sins - Chrissidis, Nikolaos A. (Canadian-american Slavic Studies, 2018)
The article explores the practical uses of Eastern Orthodox indulgences as certificates of absolution with a dual function (as mnemonic tools and as public certificates of good standing with the church) in the early modern period. © KONINKLIJKE BRILL NV, LEIDEN, 2018
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00325 tex.type: [object Object]
Keywords: Eastern Orthodox indulgences; Eastern Orthodox penitential practices; Mese katastasis ton psychon; Patriarch Dositheos of Jerusalem; Purgatory; Synchorochartia; dept.his; peer-reviewed

“Notorious abuse,” “traditious ignorance,” and “ambitious incroachment” in seventeenth-century Dutch, English, and French maps of North America - Petto, Christine M. (Cartographica: The International Journal for Geographic Information and Geovisualization, 2018)
In consideration of Richard Daniel’s alarmed discourse found in the text accompanying his map of the English empire in America (1679), one must investigate the supposedly offending French, English, and Dutch maps of the second half of the seventeenth century for North America and, in particular, the region of the Atlantic coastline and the rhetorical devices of possession found on or in these geographical works. In addition to looking at territorial boundaries, one should also make note of armorial bearings, ships with naval ensigns, toponyms and their placement on the territory, dedicatory cartouches, legends with geographical or historical information, native scenes, and symbols for settlement. In addition to attention to possible constraints on or from the map trade, one must consider the correspondence between colonial officials and their respective governments regarding boundaries, encroachment, sovereignty, or the need for maps with a particular focus on the North American coastline. This correspondence reflects the state’s point of view, which in turn was often manifested on maps and in geographical works. Interestingly intertwined with this outspoken sense of rightful possession were the contemporary claims from some quarters that the cartographic enterprise of the late seventeenth century now embraced an empirical approach, as well as the seemingly opposing thread of the economic realities of the print trade, which often used old copper plates with little to no cartographic revision, so that long after political, economic, or military actions resulted in an “adjustment” in possession, printed maps, atlases, and other geographical works still reflected earlier circumstances. © University of Toronto Press
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/051-706-928-277-117, pop00268 tex.type: [object Object]
Keywords: Cartography; Colonies; England; France; History; Netherlands; New England; New Netherland; North America; Seventeenth-century maps; The Netherlands; United Kingdom; colonialism; dept.his; economic history; empirical analysis; historical cartography; human settlement; peer-reviewed; seventeenth century; territorial dispute

War and Environment - Smith, Jason W. (The Routledge History of Global War and Society, 2018)
Scholars have offered at least four distinct but interrelated conceptual frameworks for examining the relationship between militaries and the natural world.
Keywords: dept.his

Hope in an ad: Teaching consumerism and idealized womanhood using 1920s advertisements - Carter-David, Siobhan (Advertising & Society Quarterly, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Computer systems: Digital design, fundamentals of computer architecture and assembly language - Elahi, Ata (Springer International Publishing, 2018)
This textbook covers digital design, fundamentals of computer architecture, and assembly language. The book starts by introducing basic number systems, character coding, basic knowledge in digital design, and components of a computer. The book goes on to discuss information representation in computing; Boolean algebra and logic gates; sequential logic; input/output; and CPU performance. The author also covers ARM architecture, ARM instructions and ARM assembly language which is used in a variety of devices such as cell phones, digital TV, automobiles, routers, and switches. The book contains a set of laboratory experiments related to digital design using Logisim software; in addition, each chapter features objectives, summaries, key terms, review questions and problems. The book is targeted to students majoring Computer Science, Information System and IT and follows the ACM/IEEE 2013 guidelines. • Comprehensive textbook covering digital design, computer architecture, and ARM architecture and assembly • Covers basic number system and coding, basic knowledge in digital design, and components of a computer • Features laboratory exercises in addition to objectives, summaries, key terms, review questions, and problems in each chapter
Citation Key Alias: elahiComputerSystemsDigital2017
Keywords: ARM architecture; ARM processors; Assembly language; Boolean algebra; Computation theory; Computer architecture; Digital designs; Digital devices; Digital television; Information representation; Laboratory exercise; Laboratory experiments; Number system; Numbering systems; Reviews; Sequential logic; Textbooks; dept.csc

Confucius and filial piety - Radice, Thomas (A Concise Companion to Confucius, 2017)
Keywords: dept.his

Dreams of antiquity: H. P. Lovecraft’s great Roman dream of 1927 - Nakamura, Byron (Lovecraftian Proceedings No. 2, 2017)
This second volume of Lovecraftian Proceedings contains a wealth of cutting-edge scholarship on the dreamer from Providence, including substantial articles from both recipients of the S. T. Joshi Endowed Research Fellowship for H. P. Lovecraft at Brown University. Lovecraftian Proceedings fosters exploration of Lovecraft as a rationalist who created an elaborate cosmic mythology, and how this mythology was influenced by, and has come to influence, numerous other authors and artists. The papers which comprise Lovecraftian Proceedings were presented during a key part of the NecronomiCon Providence convention, the Dr. Henry Armitage Memorial Symposium. TABLE OF CONTENTS Introduction Dennis P. Quinn Dreams of Antiquity: H. P. Lovecraft's Great Roman Dream of 1927Byron Nakamura The Poet’s Nightmare: The Nature of Things According to LovecraftSean Moreland Reordering the Universe: H. P. Lovecraft’s Subversion of the Biblical DivineRené J. Weise Resisting Cthulhu: Milton and Lovecraft’s Errand in the Wilderness Marcello Ricciardi “The Discriminating Urban Landscapist": Tradition and Innovation in the Architectural Writings of H. P. LovecraftConnor Pitetti Tentacles in the Madhouse: The Role of the Asylum in the Fiction of H. P. LovecraftTroy Rondinone Unspeakable Languages: Lovecraft Editions in Spanish Juan L. Pérez-de-Luque Color out of Mind: Correlating the Cthulhu Mythos Universe to the Autism Disorder SpectrumLars G. Backstrom Darwin and the Deep Ones: Anthropological Anxiety in "The Shadow over Innsmouth" and Other StoriesJeffrey Shanks The “Inside” of H. P. Lovecraft’s Supernatural Horror in the Visual Arts Nathaniel R. Wallace H. P. Lovecraft’s OptimismMatthew Beach Insider, Outsider: From the Commonplace to the Uncanny in H. P. Lovecraft’s Narration and DescriptionsDaphnée Tasia Bourdages-Athanassiou H. P. Lovecraft, Georges Bataille, and the Fascination of the Formless: One Crawling Chaos Seen Emerging from Opposite ShoresChristian Roy Ripples from Carcosa: H. P. Lovecraft, True Detective, and the Artist-InvestigatorHeather Poirier Lovecraft for the Little Ones: ParaNorman, Plushies, and MoreFaye Ringel and Jenna Randall Contributors AppendixAbstracts of Papers Presented at the Dr. Henry Armitage Memorial Scholarship Symposium,NecronomiCon Providence 20-23 August, 2015Chair: Dennis P. Quinn Index
Keywords: dept.his

Li (ritual) in early Confucianism - Radice, Thomas (Philosophy Compass, 2017)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-883-856-156-766, pop00371 tex.type: [object Object]
Keywords: dept.his

The implications of gia truyền: Family transmission texts, medical authors, and social class within the healing community in Vietnam - Thompson, C. Michele (South East Asia Research, 2017)
In Vietnamese medicine, gia truyen ("family recipes") refers to a set of texts, primarily in chu nôm (demotic Vietnamese characters), that preserves local knowledge about how practitioners in a specific family-based medical circle could use various plants and other materia medica to cure disease. This article traces the history of the transmission of gia truyen in the 19th and 20th centuries. It suggests that prior to the 1920s, gia truyen were written anonymously to protect the author's identity in the face of the Nguyen dynasty's repression of ch? nom writing. In the 1920s, precisely at the time that hán-nôm writing was being eclipsed by education in French and quoc ngu (Romanized Vietnamese), Vietnamese medical practitioners experienced a renaissance in the writing of chu nôm gia truyen. Moreover, chu nôm writing in the gia truyen genre continued until at least the 1990s. ©SOAS University of London 2017.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-172-230-163-181, pop00329 tex.type: [object Object]
Keywords: Chu nom; Colonial; Materia medica; Medical texts; Traditional medicine; Viet Nam; class; dept.his; disease treatment; historical perspective; medical geography; nineteenth century; social history; traditional knowledge; traditional medicine; twentieth century

Method mourning: Xunzi on ritual performance - Radice, Thomas (Philosophy East and West, 2017)
3 citations (Crossref) [2023-10-31]
Keywords: dept.his

The journey from discovery to scientific change: scientific communities, shared models, and specialised vocabulary - Roe, Sarah M (International Studies in the Philosophy of Science, 2017)
Scientific communities as social groupings and the role that such communities play in scientific change and the production of scientific knowledge is currently under debate. I examine theory change as a complex social interaction among individual scientists and the scientific community, and argue that individuals will be motivated to adopt a more radical or innovative attitude when confronted with striking similarities between model systems and a more robust understanding of specialised vocabulary. Two case studies from the biological sciences, Barbara McClintock and Stanley Prusiner, help motivate the idea that sharing of models and specialised vocabulary fill the gap between discovery and scientific change by promoting the dispersal of important information throughout the scientific community. © 2017 Open Society Foundation.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-085-635-391-358 tex.type: [object Object]
Keywords: dept.his

Extended mechanistic explanations: expanding the current mechanistic conception to include more complex biological systems - Roe, Sarah M; Baumgaertner, Bert (Journal for General Philosophy of Science, 2017)
Mechanistic accounts of explanation have recently found popularity within philosophy of science. Presently, we introduce the idea of an extended mechanistic explanation, which makes explicit room for the role of environment in explanation. After delineating Craver and Bechtel’s (2007) account, we argue this suggestion is not sufficiently robust when we take seriously the mechanistic environment and modeling practices involved in studying contemporary complex biological systems. Our goal is to extend the already profitable mechanistic picture by pointing out the importance of the mechanistic environment. It is our belief that extended mechanistic explanations, or mechanisms that take into consideration the temporal sequencing of the interplay between the mechanism and the environment, allow for mechanistic explanations regarding a broader group of scientific phenomena. © 2016, Springer Science+Business Media Dordrecht.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/167-521-013-773-230 tex.type: [object Object]
Keywords: Complex systems; Explanation; Mechanism; Mechanistic environment; dept.his